Liquidity and Solvency Ratio Analysis of Jk Cement Group: Examining JK Cement Group's Performance through Liquidity and Solvency Ratios (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Cement is an essential component required for the development of theinfrastructure and various housing programmes which are necessary for thesocio-economic growth and development of the country. The Indian cementindustry is the second largest producer of cement in the world but ahead of theunited statesand Japan. For over 3 decades, JK cement’s business prioritieshavebeen closely aligned with national aspirations and objectives. During thisperiod India’s economic growth and Govt. reforms have lifted millions of peoplefrom poverty and ignorance by giving them an opportunity to live life withdignity. JK cement long term vision is also the same and it has succeeded inachieving its objectives.